2014
DOI: 10.1159/000362125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consanguinity on Neonatal Outcomes and Health

Abstract: Consanguineous marriages constitute a significant fraction of marriages worldwide and confer a major public health concern on newborns. In addition to the risk of acquiring a recessive genetic disease, the offspring of consanguineous parents are plausibly at an increased risk of preterm birth, decreased anthropometric measurements, congenital defects and mortality. How consanguinity confers such an increased risk is still largely unknown. In this review, we discuss the effect of consanguinity on selected gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Preconception and prenatal counselling should be offered to consanguineous couples, who should also be reminded about regular postnatal followup examinations, in order to avoid any delay in diagnosing any developmental or behavioural disorders. 27 Pakistani ethnicity accounted for only 1.6% of all fetuses but 85% of consanguineous couples in our study. According to the Hong Kong 2016 population by-census, 0.25% of the total Hong Kong population was of Pakistani ethnicity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Preconception and prenatal counselling should be offered to consanguineous couples, who should also be reminded about regular postnatal followup examinations, in order to avoid any delay in diagnosing any developmental or behavioural disorders. 27 Pakistani ethnicity accounted for only 1.6% of all fetuses but 85% of consanguineous couples in our study. According to the Hong Kong 2016 population by-census, 0.25% of the total Hong Kong population was of Pakistani ethnicity.…”
Section: Discussionmentioning
confidence: 57%
“…Findings on the effect of consanguinity on various complications are inconsistent, especially when these complications are multifactorial in pathogenesis. 5,15,27,29,30 One limitation of our study is the retrospective nature that might have led to incompleteness of information for analysis, especially when previous pregnancies were not in Hong Kong. Another limitation is that some of the fetal abnormalities classified under category C may in fact be category B disorders, as some of them recurred in the same couples (online supplementary Appendix 1); the majority of category C disorders did not receive genetic investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population-based studies of consanguinity have demonstrated that there may be an increased risk of autosomal recessive inheritance associated with preterm birth(16, 17, 21, 22). Fine mapping of ROH has been made possible by high density SNP genotyping arrays.…”
Section: Discussionmentioning
confidence: 99%
“…15 Consanguineous marriages, the unions between bloodrelated individuals with a common ancestor, are still surprisingly prevalent in certain regions of the world, more so in India. 16 Hence in our study we have made some efforts to assess whether there was any association between the consanguinity factor and low birth weight. However, our study did not show any statistical relation in this aspect.…”
Section: Discussionmentioning
confidence: 99%